2016
DOI: 10.1186/s13058-016-0772-7
|View full text |Cite
|
Sign up to set email alerts
|

Deep targeted sequencing of 12 breast cancer susceptibility regions in 4611 women across four different ethnicities

Abstract: BackgroundAlthough genome-wide association studies (GWASs) have identified thousands of disease susceptibility regions, the underlying causal mechanism in these regions is not fully known. It is likely that the GWAS signal originates from one or many as yet unidentified causal variants.MethodsUsing next-generation sequencing, we characterized 12 breast cancer susceptibility regions identified by GWASs in 2288 breast cancer cases and 2323 controls across four populations of African American, European, Japanese,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…But this model fails to account for the lack of rare variants discovered so far in the vicinity of breast cancer-risk GWAS hits ( Lindström et al, 2016 ; Li et al, 2018 ) and the comparatively few mutations identified by linkage analysis and subsequent positional cloning ( Gonzalez-Neira et al, 2007 ; Rosa-Rosa et al, 2009a ). An alternative hypothesis is that the haplotype itself is the rare causal variant and that risk is because of the interaction of alleles at discrete locations along the haplotype.…”
Section: Discussionmentioning
confidence: 99%
“…But this model fails to account for the lack of rare variants discovered so far in the vicinity of breast cancer-risk GWAS hits ( Lindström et al, 2016 ; Li et al, 2018 ) and the comparatively few mutations identified by linkage analysis and subsequent positional cloning ( Gonzalez-Neira et al, 2007 ; Rosa-Rosa et al, 2009a ). An alternative hypothesis is that the haplotype itself is the rare causal variant and that risk is because of the interaction of alleles at discrete locations along the haplotype.…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, also possible that the rare haplotypes do not represent single risk mutations, but rare combinations of alleles whose interaction predisposes to disease. Few rare single variants have been found to explain synthetic associations of GWAS hits at breast cancer loci (11,12). Furthermore, despite the prevalence of GWAS hits, comparatively few rare mutations have been found in family-based linkage studies of breast cancer with subsequent positional cloning (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…One is the hypothesis that so-called "synthetic associations" of rare variants near GWAS hits explain observed GWAS signals (8). While theoretical and sequencing studies have not provided strong evidence for this hypothesis (9)(10)(11)(12), it has not been considered whether rare haplotypes, instead of rare variants, underlie GWAS hits. Another hypothesis is that human diseases have substantial "genetic heterogeneity," being due primarily to rare mutations, such as those of the BRCA1/2 genes, which segregate in families (13).…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is one of the most common cancers in human beings, and the incidence among women is the first. 1 So far, the incidence of breast cancer has accounted for 30% of female malignant tumor. 2 Breast cancer is the most common cancer among women of the western developed countries, while it is also increasing yearly in developing countries.…”
Section: Breast Cancer and Research Progress Of Related Genesmentioning
confidence: 99%